Nutrition, illness, and injury in aquatic sports - Pyne, D. B.; Verhagen, E. A.; Mountjoy, M. L. (International Journal of Sport Nutrition and Exercise Metabolism, 2014)
In this review, we outline key principles for prevention of injury and illness in aquatic sports, detail the epidemiology of injury and illness in aquatic athletes at major international competitions and in training, and examine the relevant scientific evidence on nutrients for reducing the risk of illness and injury. Aquatic athletes are encouraged to consume a well-planned diet with sufficient calories, macronutrients (particularly carbohydrate and protein), and micronutrients (particularly iron, zinc, and vitamins A, D, E, B6, and B12) to maintain health and performance. Ingesting carbohydrate via sports drinks, gels, or sports foods during prolonged training sessions is beneficial in maintaining energy availability. Studies of foods or supplements containing plant polyphenols and selected strains of probiotic species are promising, but further research is required. In terms of injury, intake of vitamin D, protein, and total caloric intake, in combination with treat- ment and resistance training, promotes recovery back to full health and training.